Transabdominal cerclage: preconceptual or first trimester insertion?. (16th November 2010) - Dawood, F; Farquharson, RG
Abstract : Transabdominal cerclage (TAC) is a recognised treatment for cervical weakness with a history of recurrent mid-trimester loss (MTL) and a failed vaginal suture. Methodology: A comparative study was performed of 40 women who underwent TAC in the first trimester (T1) between 1993 and 2005, with a group of 38 women who underwent preconceptual (PC) TAC between 2006 and 2008. All patients had identical inclusion criteria with ≥1 MTL and ≥1 failed elective vaginal suture and underwent a standardised investigation protocol and TAC insertion based at the Recurrent Miscarriage Clinic of Liverpool Women's Hospital. Results: PC investigation showed a similar prevalence of associated pathology with antiphospholipid syndrome or bacterial vaginosis present in 45% (18/40) and 50% (19/38) in the T1 and PC groups respectively. A history of previous cone biopsy or large loop excision of the transformation zone featured in 20% (eight) and 33% (seven) in the T1 and PC groups respectively. Complete obstetric outcomes were available for all 40 women in the T1 cohort. Of the 38 women in the PC cohort, 21 have delivered and 1 patient is currently pregnant beyond 24 weeks. Gestation at delivery First trimester TAC (n=40) Preconceptual TAC (n=21) >34/40 62% (25) 81% (17) 30–34/40 20% (8) 14% (3) 24–30/40 7% (3) 0 <24/40 10% (4) 5% (1) Overall >24/40 90% (36) 95% (20) Conclusion: PC insertion of a TAC appears to yield a more favourable pregnancy outcome than a T1 TAC and avoids significant surgical complications of T1 insertion.